The Judge's Task to Find Law Under the Indonesian Law - Peter Mahmud Marzuki (Universitas Airlangga, 2019)
Under Indonesian Law, judge is obliged to find law in addition to apply legal text. The purpose of law finding activity is to resolve the case in the event that law is silent, unclear, or obsolete in order to produce a just and acceptable solution. Read More